A study on employee retention in Syarikat Perumahan Negara Berhad and Syarikat Prasarana Negara Berhad / Noor Idayu Jasmee and Siti Athirah Shahadat - Jasmee, Noor Idayu; Shahadat, Siti Athirah (Faculty of Business and Management, 2013)
Employee retention is an effort by an employer to maintain desirable employees in order to meet the organization’s objective. This issue is a great importance as employers must compete each other in order to retain skilled employees in the organization. A study about the factors affecting employee retention was conducted amongst 123 employees of SPNB and Prasarana. In this research paper, relationship between individual based factor (work life balance & marriage), firm-based factor (career development & compensation), and market factor (economic cycle) with employee retention is investigated. The study found positive but insignificant relationship between marriage and economic cycle. Recommendation for future research is also been discussed beneficial for the company to upgrade information about employee retention.